Dinamika Utang Luar Negeri Indonesia Dan Risiko Stabilitas Ekonomi Jangka Panjang - Ensellina Mas’ul; Anggi Salma Septiningtyas; Rosilah Rosilah; Syafaatul Hidayati (CV. SINAR HOWUHOWU, 2026)
This study aims to analyze the dynamics of Indonesia’s external debt and its implications for long-term economic stability from a macroeconomic perspective. The increasing trend of external debt in developing countries, including Indonesia, has become an important issue related to fiscal sustainability, exchange rate stability, inflation, and economic growth. This research employs a qualitative approach through literature review by examining scientific journals, government reports, and macroeconomic publications issued within the last five years. The findings indicate that external debt contributes positively to national development when allocated productively, especially in infrastructure financing and economic recovery programs. However, excessive dependence on external debt may increase fiscal pressure, weaken exchange rate stability, and create vulnerability to global economic shocks. The study concludes that prudent debt management policies, strengthening domestic revenue, and improving export competitiveness are important strategies to maintain Indonesia’s long-term macroeconomic stability amid global uncertainty.